2006
DOI: 10.1002/chin.200609022
|View full text |Cite
|
Sign up to set email alerts
|

Effects of SWNT and Metallic Catalyst on Hydrogen Absorption/Desorption Performance of MgH2.

Abstract: The microstructure and absorption/desorption characteristics of composite MgH 2 and 5 wt % as-prepared single-walled carbon nanotubes (MgH 2 -5ap) obtained by the mechanical grinding method were investigated. Experimental results show that the MgH 2 -5ap sample exhibits faster absorption kinetics and relatively lower desorption temperature than pure MgH 2 or MgH 2 -purified single-walled carbon nanotube composite. Storage capacities of 6.0 and 4.2 wt % hydrogen for the MgH 2 -5ap composite were achieved in 60 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 24 publications
0
5
1
Order By: Relevance
“…In addition, a combination of active metal nanoparticles and nanostructured carbon materials as mixed dopants is an effective catalyst for enhancement of the hydrogen storage properties of metal hydrides and complex hydrides, as reported in the literatures. ,, The unique nanostructure of the CNT is expected to form a net-like architecture after being milled together with the host materials and acting as a diffusion channel for hydrogen, while the metal nanoparticles have high catalytic activity. , In this study, the enhancement of the CNT-added MgH 2 –FeCl 3 sample may also have been due to the hardness of the CNT. The presence of the CNT in the MgH 2 –FeCl 3 composite prevented particle agglomeration, as shown above in Figure c.…”
Section: Resultsmentioning
confidence: 52%
See 1 more Smart Citation
“…In addition, a combination of active metal nanoparticles and nanostructured carbon materials as mixed dopants is an effective catalyst for enhancement of the hydrogen storage properties of metal hydrides and complex hydrides, as reported in the literatures. ,, The unique nanostructure of the CNT is expected to form a net-like architecture after being milled together with the host materials and acting as a diffusion channel for hydrogen, while the metal nanoparticles have high catalytic activity. , In this study, the enhancement of the CNT-added MgH 2 –FeCl 3 sample may also have been due to the hardness of the CNT. The presence of the CNT in the MgH 2 –FeCl 3 composite prevented particle agglomeration, as shown above in Figure c.…”
Section: Resultsmentioning
confidence: 52%
“…Previous studies have shown that the carbon nanotube (CNT) is a good catalyst for MgH 2 . , In addition, a combination of transition metals with CNTs as mixed dopants has been found to lead to significant improvement of hydrogen dissociation and diffusion in nanostructured magnesium. This indicates that the synergistic interaction among CNTs and metals may be an effective approach to improve the hydrogen storage properties of MgH 2 . Although the hydrogen storage properties of MgH 2 were improved, it still does not satisfy all of the requirements for practical applications.…”
Section: Introductionmentioning
confidence: 99%
“…13 The TiF 3 , TiCl 3 (99.999%), TiH 2 (98%, ∼325 mesh), and Ti (99.98%, ∼325 mesh) powders were all purchased from Sigma-Aldrich Corp. (St. Louis, MO) and were used as received. The MgF 2 (97%) and NH 4 F (96%) powders were purchased from Sinopharm Chemical Reagent Corp. (Shanghai, China).…”
Section: Methodsmentioning
confidence: 99%
“…It is found that the addition of H-storage alloys, transition metals and/or their oxides, fluorides, and even some nonmetal materials through mechanical milling may all accelerate the absorption/desorption processes of MgH 2 . [2][3][4][5][6][7][8][9][10][11][12][13] However, most of the reports in the literature focused on improvement at relatively high temperatures (usually higher than 473 K). Only a few reports concern the substantial improvement in kinetics achieved in a moderate operation temperature range lower than 373 K, which is of practical interest for on-board H-storage application.…”
Section: Introductionmentioning
confidence: 97%
“…In the past several decades, various hydrogen storage materials, such as metal hydrides [1,2], nanocarbon materials [3], metal-N-H systems [4][5][6][7], have been studied. Unfortunately, no known material meets all of the technical requirements for a practical hydrogen storage system for fuel cell vehicles.…”
Section: Introductionmentioning
confidence: 99%